The Organization of Islamic Cooperation (OIC): Opportunities and Challenges for Practicing Culturally-Sensitive Mediation in Intra-Muslim Conflicts - Ahmad, Nirvana (AUC Knowledge Fountain, 2023)
Established in 1969, the OIC sat a unique paradigm in the international order as an intergovernmental organization that claims a religious identity and mandate: working for Muslim unity and interests. In that pursuit, it has assumed the function of the peaceful settlement of disputes as one of its primary roles. Over half a century of its existence, not only did the OIC drift away from its founding principles and commitments; it is now condemned for turning into an arena for polarization among Muslims, where unchecked geopolitical competition has aroused rampant violence of all sorts. The literature on the OIC extensively discussed the declined potency of the shared faith of Islam as a unification norm, its inhibiting effect on the organization’s operational framework, in addition to religion becoming a source for division and radicalizm. In contrast, this research offers to demonstrate that operating on the Islamic norms in conflict management and peacemaking, through the engagement of religious leaders, is the viable mechanism by which the OIC can play an effective role in Intra-Muslim disputes and effectually deploy its idiosyncratic resources within the United Nations system.In this quest, this thesis explores the prospects of the OIC - as a faith-based organization- to exercise a more efficient mediatory role in intra-Muslim conflicts, through staging culturally-sensitive interventions. It examines the organization’s potential to exercise such a role amid cultural domination, the supremacy of realpolitik, and the lack of an ideological and normative framework.